HISTOPATHOLOGICAL CHANGES INDUCED BY MANGANESE IN RAT TESTES - KATIRA, V.; BAWA, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
Testicular damage was produced in ratsbysubcutaneous administration of manganese chloride (3 mg/kg) for a period of three weeks. Histopathological examination after three weeks revealed a disturbed spermatogenesis in the testes. It is suggested that possibly manganese has a specific, direct action on the spermatogenic epithelium.